1997
DOI: 10.1152/ajprenal.1997.273.4.f516
|View full text |Cite
|
Sign up to set email alerts
|

A conserved cytoplasmic region of ROMK modulates pH sensitivity, conductance, and gating

Abstract: ROMK channels play a key role in overall K balance by controlling K secretion across the apical membrane of mammalian cortical collecting tubule. In contrast to the family of strong inward rectifiers (IRKs), ROMK channels are markedly sensitive to intracellular pH. Using Xenopus oocytes, we have confirmed this pH sensitivity at both the single-channel and whole cell level. Reduction of oocyte pH from 6.8 to 6.4 (using a permeant acetate buffer) reduced channel open probability from 0.76 ± 0.02 to near zero ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
183
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(200 citation statements)
references
References 11 publications
15
183
1
Order By: Relevance
“…2 A). Similar observations for ROMK1 and ROMK2 have been reported by others (8,10). The half-maximal inhibitory pH values, pH 0.5 , and Hill coefficients of the isoforms were not significantly different (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2 A). Similar observations for ROMK1 and ROMK2 have been reported by others (8,10). The half-maximal inhibitory pH values, pH 0.5 , and Hill coefficients of the isoforms were not significantly different (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1) produced pH-insensitive channels (8,10,14); however, a more complete pH titration to 4 demonstrated that each of the three ROMK isoforms remained pH sensitive, with the N-terminal K3 M mutation ( Fig. 2 B and C).…”
Section: Resultsmentioning
confidence: 95%
“…pH i sensitivity has been observed in members of the K ir (12,39), the K Ca (31,49), and the K v (6) channel family. pH o sensitivity has been observed in members of the TASK channel family (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…A strategy that has been well documented for acidifying oocytes uses acetate-buffered solutions. In the presence of 60 mM sodium acetate, the lipophilic protonated form of acetic acid crosses the membrane and dissociates, acidifying intracellular pH i (14,15). After 20 -25 min of incubation in acetate buffer the pH i reaches steady state and recovers on removal in ϳ15 min (14).…”
Section: Rhag-mediated Ma Uptake Is Not Dependent On Membrane Potentimentioning
confidence: 99%
“…In the presence of 60 mM sodium acetate, the lipophilic protonated form of acetic acid crosses the membrane and dissociates, acidifying intracellular pH i (14,15). After 20 -25 min of incubation in acetate buffer the pH i reaches steady state and recovers on removal in ϳ15 min (14). Oocytes were preincubated for 25 min in acetate buffers adjusted from pH 6.1 to 7.4 and then moved to MA uptake buffer at pH 7.5 or 8.5, a treatment that is expected to lower pH i to approximately pH 5.9 -6.8 (14).…”
Section: Rhag-mediated Ma Uptake Is Not Dependent On Membrane Potentimentioning
confidence: 99%